2016
DOI: 10.5152/balkanmedj.2015.150089
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Granulomatous Mastitis Associated with Erythema Nodosum

Abstract: Background: Idiopathic granulomatous mastitis (IGM) is an uncommon benign chronic inflammatory breast disease, and erythema nodosum (EN) is an extremely rare systemic manifestation of IGM. Here, we report a rare case of IGM accompanied by EN. Case Report: A 32-year-old patient was admitted to our clinic with a history of a tender mass in the right breast. On physical examination, the right breast contained a hard, tender mass in the lower half with indrawing of the nipple. She had florid EN affecting both legs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…8 The EN and IGM association is rare, reported with case reports and series. [9][10][11][12][13][14][15] Additionally, to the best of our knowledge, it is the only systemic and extra-breast finding of IGM. However, no studies were reported before elaborating the significance of both entities' coexistence on the severity of IGM and response to conventional treatment.…”
Section: Introductionmentioning
confidence: 99%
“…8 The EN and IGM association is rare, reported with case reports and series. [9][10][11][12][13][14][15] Additionally, to the best of our knowledge, it is the only systemic and extra-breast finding of IGM. However, no studies were reported before elaborating the significance of both entities' coexistence on the severity of IGM and response to conventional treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The disease, was first described by Kessler and Wollock in 1972 ( 5 ). Although it is a benign condition, it is important from different points of view: 1-it poses a diagnostic and treatment dilemma ( 2 , 3 ), also, it clinically and mammographically mimics breast cancer, especially inflammatory type ( 4 ). On the other hand, due to lack of a definitive treatment plan, complications of empiric treatment, such as allergic reaction to antibiotics and poor cosmetic procedures result in following repeated surgical interventions which threaten the patients ( 2 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Idiopathic granulomatous mastitis is a rare benign chronic inflammatory disease of breast that involves mainly women of childbearing age. 1,2,3,4 The disease, was first described by Kessler and Wollock in 1972. 5 The etiopathogenesis of IGM is unknown but some factors causing reaction to chemical materials such as OCP, infectious disease, autoimmune diseases and immunologic response for milk leakage from the breast's lobule.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…5 The etiopathogenesis of IGM is unknown but some factors causing reaction to chemical materials such as OCP, infectious disease, autoimmune diseases and immunologic response for milk leakage from the breast's lobule. 3,6 Also conditions like pregnancy, breast feeding, hyperprolactinemia, galactorrhoea, and alpha 1 antitrypsin deficiency have been associated with the risk of the disease. Most common clinical features are breast mass, pain, skin changes, axillary lymphadenopathy, inflammation may not always be present clinically, thus leading to misdiagnosis as a malignant lesion.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%